2016
DOI: 10.1007/s00436-016-5128-9
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of Babesia microti ‘Munich’ type in small mammals from an Ixodes persulcatus/Ixodes trianguliceps sympatric area in the Omsk region, Russia

Abstract: Babesia microti is a genetically diverse group of protozoan parasites whose life cycle is associated with both small mammals and Ixodes spp. ticks. In this study, the prevalence of different B. microti genetic groups in ticks and small rodents in an area with Ixodes persulcatus and Ixodes trianguliceps occurring in sympatry was examined. A total of 541 small mammals were captured during eight sampling periods between 2013 and 2015 at a site in the Omsk region of Russia and tested for the presence of B. microti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Our present study revealed that both Kobe-type and U.S.-type B. microti were prevalent in small mammalian hosts from Beijing based on the large number of samples tested (Tables 1 and 2)-with Kobe-type more prevalent than U.S.-type. As is known, B. microti has been recognized as a genetically diverse complex group, generally clarified into U.S.-, Munich-, Kobe-, and Hobetsu-(or Ostu-) types [20,28,29]. In Beijing, only Kobe-type B. microti, was detected from small rodents in Miyun, and documented previously [11].…”
Section: Discussionmentioning
confidence: 54%
“…Our present study revealed that both Kobe-type and U.S.-type B. microti were prevalent in small mammalian hosts from Beijing based on the large number of samples tested (Tables 1 and 2)-with Kobe-type more prevalent than U.S.-type. As is known, B. microti has been recognized as a genetically diverse complex group, generally clarified into U.S.-, Munich-, Kobe-, and Hobetsu-(or Ostu-) types [20,28,29]. In Beijing, only Kobe-type B. microti, was detected from small rodents in Miyun, and documented previously [11].…”
Section: Discussionmentioning
confidence: 54%
“…The duration of B. microti infection in naturally infected ( via tick vector) P. leucopus is unclear; however, chronic infection has been shown to persist in laboratory P. leucopus for seven months and possibly longer [ 9 , 10 , 28 , 29 ]. Chronic infection of B. microti was also observed for approximately five months in naturally infected voles from Russia [ 30 ]. In these ways mice infected over the transmission season (April-July) could remain infected until the following spring, when transplacental transmission could further increase early-season transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that dogs and cats may contribute substantially to the circulation of the pathogen among ticks. Some small mammals, such as voles [22] and other rodents [23], are also involved in the enzootic maintenance and transmission of B. microti .…”
Section: Discussionmentioning
confidence: 99%